Analysis of Students' Mathematical Problem-Solving Ability Based on Category Levels Through Polya Steps - Taneo, Prida N. L.; Kusumah, Yaya S (IKIP Siliwangi, 2021)
This study aims to describe students' mathematical problem-solving abilities based on the category level through the Polya steps. the stages of solving the problem pattern consist of the stage of understanding the problem, planning solutions, and checking again. The subject of this study chose six people from thirty-one students from class VIII SMP Negeri 1 Soe. Data collection by conducting tests and interviews. the results showed that the upper category students did not experience difficulties at the stage of understanding the problem and making plans, while at the stage of implementing the plan there were still parts that were not done because they felt that they were not needed, while at the stage of re-examining students in the upper category they did not do it. students in the medium category can already understand the plan well, while at the planning stage it has not been fully carried out, so at the stage of implementing the plan not all of them can do well either, for the medium category no one checks again. students with low categories have not been able to fully understand the problem and make plans, so they cannot carry out the plan and also cannot check back on what has been done. Subjects with high score categories have been able to solve problems even though they are still not perfect, subjects with moderate value categories have sufficient problem-solving abilities, and subjects with low-value categories have very poor problem-solving abilities.